News for action: a critical case study of Yes! magazine - Hosford-Israel, Carly (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2021)
Coming out of more than a century of concern over the commercialization and monopolization of media ownership, this study highlights some areas of opportunity for alternative media in the United States. Holding an ideal of participatory democracy, driven by an educated electorate, the research considers an example of US media action, Ye s ! magazine, from the perspective of alternative media and social movement theories. As alternative media are most generally a response to the mainstream model which acts in the interests of profit rather than public participation in politics, this thesis will cover not only democratic responsibility, but also mainstream media ownership and organization when considering the current manifestation of Ye s ! magazine. Inspired by a frustration with the concentration of mainstream media ownership, and consequently journalistic homogenization, this research explores opportunities for democratic media divergence and contestation. After 18 years of publication, Ye s ! was chosen as an ideal candidate for research due to its sustainability and longevity as one such critical media organization. Through in-depth interviews with Yes! personnel, and ideological analysis of Yes! articles, the following case study research explores the complexities that construct Ye s ! magazine, a corporately independent publication from Bainbridge Island, Washington.
Keywords: Yes! (Bainbridge Island, WA); Magazines -- United States -- History and criticism; Journalistic ethics; Journalism -- Social aspects -- United States; Journalism -- Objectivity; Mass media -- Ownership -- United STates; Publishers and publishing -- United States